2013
DOI: 10.1177/1933719112459233
|View full text |Cite
|
Sign up to set email alerts
|

Fibroid-Associated Heavy Menstrual Bleeding: Correlation Between Clinical Features, Doppler Ultrasound Assessment of Vasculature, and Tissue Gene Expression Profiles

Abstract: Despite the prevalence of uterine fibroids (Fs), few studies have investigated the links between clinical features and the cellular or molecular mechanisms that drive F growth and development. Such knowledge will ultimately help to differentiate symptomatic from asymptomatic Fs and could result in the development of more effective and individualized treatments. The aim of this study was to investigate the relationship between ultrasound appearance, blood flow, and angiogenic gene expression in F, perifibroid (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
15
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 42 publications
1
15
0
3
Order By: Relevance
“…The capsule of the fibroid surrounds the fibroid and at the same time can be seen as a different entity. It has been a subject of interest and has been studied from different perspectives using different techniques (histopathological, immunohistochemical, [angiogenic] gene expression, growth factors, neurotransmitters, imaging techniques) . In this study no correlation was found between fibroid capsule vascularisation and fibroid growth.…”
Section: Discussionmentioning
confidence: 60%
“…The capsule of the fibroid surrounds the fibroid and at the same time can be seen as a different entity. It has been a subject of interest and has been studied from different perspectives using different techniques (histopathological, immunohistochemical, [angiogenic] gene expression, growth factors, neurotransmitters, imaging techniques) . In this study no correlation was found between fibroid capsule vascularisation and fibroid growth.…”
Section: Discussionmentioning
confidence: 60%
“…Tsiligiannis et al [ 32 ] reported that the mean PSV was significantly higher in the perifibroid region than within the fibroids (30.2 vs. 12.0 cm/s; P <0.001). This is in agreement with our results though we recorded much higher PSV values (54 vs. 45 cm/s; P <0.001), presumably because the leiomyoma nodules in this study are larger.…”
Section: Discussionmentioning
confidence: 99%
“…Кроме того, ЛМ у одной и той же женщины растут различными темпами и обладают разной способностью к регрессу, несмотря на единообразную гормональную и паракринную среду [21]. Более того, такие характеристики, как размер, локализация и выраженность васкуляризации, определяемая ультрасонографически, не коррелируют с ростом миомы, маточным кровотечением или другой симптоматикой [21,22] ПАТОФИЗИОЛОГИЯ МИОМЫ В последние годы в качестве решающих факторов, контролирующих рост опухолей, рассматриваются ангиогенез и васкуляризация [24]. Классические исследования показывают, что миомы матки имеют аномальную сосудистую сеть и, как правило, гораздо менее васкуляризированы, чем окружающий миометрий [25,26,27].…”
unclassified
“…Авторы предположили, что эта область сосудистой капсулы, вероятно, соответствует периферическому краю хорошо васкуляризированных сосудов, наблюдаемых при УЗИ, и используется как плоскость разграничения тканей при миомэктомии. Недавно также сообщалось, что область «псевдокапсулы» имеет увеличенный кровоток по сравнению с миомой, измеряемый доплеровским ультразвуком [52].…”
unclassified